2014
DOI: 10.1111/jpn.12231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding deoiled mahua (Bassia latifolia) seed cake on the growth performance, digestibility and balance of nutrients in cross‐bred calves during pre‐patent period of Fasciola gigantica infection

Abstract: A study was conducted to assess the growth performance and nutrient utilization of cross-bred calves serially infected with Fasciola gigantica and/or supplemented with deoiled mahua seed cake (DMSC) during pre-patent period of infection. Twenty healthy cross-bred (Holstein Friesian × Haryana) male calves aged 6-7 months with an initial average live weight of 79.6 ± 2.71 kg were divided into four treatment groups (CON, CON-INF, DMC and DMC-INF) of five animals each following randomized block design. DMSC was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Hence, incorporation of 30% MOC not only yielded significant growth performance and least FCR, but also replaced the conventional ingredients like GNOC and rice bran at 120 and 180 g kg -1 respectively. Ojha et al (2013) and Jacob et al (2015) reported better growth of crossbred calves with 10% of MOC incorporation. Tiwari et al (1996) incorporated raw MOC at 20% level in the crossbred calves without affecting body weight gain.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, incorporation of 30% MOC not only yielded significant growth performance and least FCR, but also replaced the conventional ingredients like GNOC and rice bran at 120 and 180 g kg -1 respectively. Ojha et al (2013) and Jacob et al (2015) reported better growth of crossbred calves with 10% of MOC incorporation. Tiwari et al (1996) incorporated raw MOC at 20% level in the crossbred calves without affecting body weight gain.…”
Section: Discussionmentioning
confidence: 96%
“…Limited literature is available on the use of MOC in ruminant feed. Incorporation of raw MOC as one of the feed ingredients at 10-20% in cattle gives significantly higher growth performance (Jakhmola et al, 1987;Tiwari et al,1996;Singh et al, 2011;Patil et al, 2013;Jacob et al, 2015). No literature is available on the use of MOC as feed ingredient for fish feed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found similar effects of fluke infection on daily weight gain in beef cattle, although most have used data from experimental infections. These effects range from negligible (Echevarria, et al ., 1992) to substantial effects of a 0.1kg/day difference between infected and uninfected animals (Jacob, et al ., 2015) and a difference of 0.7kg/day in Belgian Blue bulls experimentally infected on a feedlot (Genicot, et al ., 1991). Meanwhile, a previous study using data from the same abattoir as used in the present study – albeit with a smaller sample size of 619 cattle – found substantial effects of fluke infection, with animals with fibrosis scores of 1, 2 and 3 taking on average 34, 93, and 78 days longer to reach slaughter weight, respectively (Mazeri, et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%